STRATEGI PEMBELAJARAN EKSPOSITORI BERMEDIA VIDEO TERHADAP HASIL BELAJAR MATEMATIKA ANAK TUNAGRAHITA SEDANG DI SLB - VIDIYANTI, WIKA (Jurnal Pendidikan Khusus, 2016)
AbstractMid mentally retardation children in SLB Merdeka Sidoarjo had difficulty in learning mathematics they needed the exact learning strategy to enhance the result of learning mathematics. The learning strategy which would be use was the strategy of expository learning with video media. The purpose of this research was to prove the influence of expository learning strategy with video media toward the result of learning mathematics to mid mentally retardation children in SLB Merdeka Sidoarjo.The method of this research used the quantitative approach of pre experiment kind with “pre experimental design (non design)”, “one group pre test – post test design”, the data collected by using test method (writing test and oral test), observation and documentation, observation was used to gain the data of the ability of learning mathematics result to mid mentally retardation children before giving treatment and after giving treatment while the data of documentation was as the supporting data or proof that the research was really done.The research result indicated that the initial observation / pre test obtained was averagely 203,2 and after giving treatment the last observation / pos test obtained was averagely 316,2. It indicated that there was significant enhancement. Zh value = 2,20 was greater than critic value 5% Zt = +1,96 which meant that Ho was refused and Ha was accepted. So it could be concluded that there was influence of learning expository strategy with video media toward the result of learning mathematics to mid mentally retardation children in SLB Merdeka Sidoarjo.Keywords: expository strategi, the result of leraning mathematics